1996
DOI: 10.1515/hfsg.1996.50.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of TCF Effluents from Kraft Pulp Bleaching. I. Fractionation of Hardwood Lignin-Derived Material by GPC and UF

Abstract: The average molecular weights (MWs) and molecular-weight distributions of lignin dissolved during different stages of the industrial totally chlorine-free (TCP) bleaching (OXZE op AEpS) of hardwood kraft pulp were compared by gel permeation chromatography (GPC) with an adequate calibration. The weight-average and number-average MWs of the total effluents from the different stages were within the ranges M w ~ 700-5,350 and M n -350-1,350. The average MWs of lignins from the stages Z and A (M w 7 00-1,500) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Detection was performed using a Waters 996 photodiode array (PDA) detector within the wavelength range 240 nm to 400 nm, and a wavelength of 280 nm was used for the determination of relative molar masses. Calibration of the GPC system was performed with a commercial set of protein standards (Sigma-Aldrich) and a number of lignin-like monomer/oligomer model compounds (Ristolainen et al 1996).…”
Section: Analysis Of the Blsmentioning
confidence: 99%
“…Detection was performed using a Waters 996 photodiode array (PDA) detector within the wavelength range 240 nm to 400 nm, and a wavelength of 280 nm was used for the determination of relative molar masses. Calibration of the GPC system was performed with a commercial set of protein standards (Sigma-Aldrich) and a number of lignin-like monomer/oligomer model compounds (Ristolainen et al 1996).…”
Section: Analysis Of the Blsmentioning
confidence: 99%
“…Detection was performed using a Waters 996 photodiode array (PDA) detector within a wavelength range of 240 nm to 400 nm, and 280 nm was used for the determination of molar masses (MMs). Calibration of the GPC system was performed with a commercial set of protein standards (SigmaAldrich, St. Louis, USA) and a number of lignin-like monomer/oligomer model compounds including vanillin (Fluka Chemical Corporation, Buchs SG, Switzerland), dehydrodiacetovanillone (synthesized in the laboratory), rutin (Aldrich Chemical Company, Milwaukee, WI, USA), and tannic acid (Lancaster Synthesis, Morecambe, England) (Ristolainen et al 1996). …”
Section: Analysis Of Extracted Ligninmentioning
confidence: 99%
“…Ristolainen and Alén (1998) found that carboxylated species in solution after TCF bleaching of pine kraft pulp were low molecular mass compounds such as formic, acetic, glyconic, and 3-hydroxypropanoic acids. In another study these authors determined lignin species in TCF effluents to have molecular masses within the range of 700 to 5350 g/mole, depending on the bleaching stage (Ristolainen et al 1996). Sulfonated lignin species have been found to interact strongly with cationic polyelectrolytes.…”
Section: Lignin-related Contributors To Cationic Demandmentioning
confidence: 99%